2021
DOI: 10.3390/ijms23010165
|View full text |Cite
|
Sign up to set email alerts
|

Neurodegeneration and Astrogliosis in the Human CA1 Hippocampal Subfield Are Related to hsp90ab1 and bag3 in Alzheimer’s Disease

Abstract: Alzheimer’s disease (AD), the most prevalent neurodegenerative disorder, is characterized by executive dysfunction and memory impairment mediated by the accumulation of extracellular amyloid-β peptide (Aβ) and intracellular hyperphosphorylated tau protein. The hippocampus (HIPP) is essential for memory formation and is involved in early stages of disease. In fact, hippocampal atrophy is used as an early biomarker of neuronal injury and to evaluate disease progression. It is not yet well-understood whether chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 72 publications
1
18
0
Order By: Relevance
“…Bioinformatics analysis indicated that the downregulation of PPP3R1 can serve as novel biomarkers for patients with AD and the potential mechanisms of low PPP3R1 involved in AD pathogenesis mainly involve in axon guidance, glutamatergic-mediated synapses transport, LTP, and MAPK signaling pathway ( 62 ). HSP90AB1, which is a chaperone of Hsp90 family that is closely linked to astrocytes, was reported to be a neuroprotective factor in AD patients via reducing the accumulation of cerebral Aβ and tau ( 63 ). As a vital chemokine, a higher concentration of CXCR10 was observed in the brain tissues of AD animal models, indicating its pathogenic role in contributing to AD progression ( 64 ).…”
Section: Discussionmentioning
confidence: 99%
“…Bioinformatics analysis indicated that the downregulation of PPP3R1 can serve as novel biomarkers for patients with AD and the potential mechanisms of low PPP3R1 involved in AD pathogenesis mainly involve in axon guidance, glutamatergic-mediated synapses transport, LTP, and MAPK signaling pathway ( 62 ). HSP90AB1, which is a chaperone of Hsp90 family that is closely linked to astrocytes, was reported to be a neuroprotective factor in AD patients via reducing the accumulation of cerebral Aβ and tau ( 63 ). As a vital chemokine, a higher concentration of CXCR10 was observed in the brain tissues of AD animal models, indicating its pathogenic role in contributing to AD progression ( 64 ).…”
Section: Discussionmentioning
confidence: 99%
“…LMNA (lamin A/C) [187], PFKFB3 [188], TRAF2 [189], ADORA2B [190], ACADS (acyl-CoA dehydrogenase short chain) [191], IRF7 [192], ASL (argininosuccinatelyase) [193], IL15 [194], PIK3R1 [195], OSM (oncostatin M) [196], SOCS3 [197], CHD9 [198], IFI44L [199], GNLY (granulysin) [200], FLNB (filamin B) [201], IL1R1 [202], SETD3 [203], TP53 [204], BRD4 [205], COX2 [206], HSP90AB1 [207], SLC7A1 [208], ND2 [209] and COX1 [210] have been reported to be associated with hypertension. LMNA (lamin A/C) [211], INPP5K [212], SCYL1 [213], AKR7A2 [214], TRAF2 [215], SLC11A2 [216], NEU1 [217], SNAP29 [218], DUSP22 [219], P2RX4 [220], ADORA2B [221], NAXD (NAD(P)HX dehydratase) [222], FEZ1 [223], TBK1 [224], GRN (granulin precursor) [225], ATG4D [226], CTSD (cathepsin D) [227], PPP2R5D [228], IRF7 [229], ACAA1 [230], S1PR1 [231], PGRMC1 [169], MAPK14 [232], IL15 [233], OSM (oncostatin M) [234], GBA (glucosylceramidase beta) [235], SOCS3 [236], GLUL (glutamate-ammonia ligase) [175], MON1A [237], LMAN2L [238], RHOC (ras homolog family member C) [239], TUBB2A [240], CHP1 [241], TP53 [242], ATXN1 [243], JARID2 [244], IFNG (interferon gamma) [245], NUCKS1 [246], CTBP1 [247], DNAJC3 [180], ATP6 [248], BRD4 [249], EIF4B [250], COX2 [251], SFPQ (splicing factor proline and glutamine rich) [252], PCBP1 [253], RPL5 [254], HSP90AB1 [255], TRA2A […”
Section: Discussionmentioning
confidence: 99%
“…Prior to morphometric analyses, we delimited the hippocampal subfields of the dentate gyrus, CA 3/2, and CA 1. These regions were delimited following the anatomical criteria described in previously published papers [ 6 , 45 , 46 ]. To ensure the accuracy of the region delimitation, we overlaid the ISH images with the corresponding Nissl sections using the software FIJI ImageJ version 1.52p (National Institutes of Health, Bethesda, MD, USA).…”
Section: Methodsmentioning
confidence: 99%